Zróżnicowanie struktur wymieralności populacji z mezolitu, neolitu i wczesnych okresów epoki brązu z terenu Europy Środkowej i Ukrainy: Próba nowego podejścia metodycznego - Piontek, Janusz; Wiercińska, Alina; Wierciński, Andrzej (Polskie Towarzystwo Antropologiczne, 1996)
DIFFERENTIATION OF THE MORTALITY STRUCTURE'IN MESOLITHIC, NEOLITHIC AND EARLY BRONZE AGE POPULATIONS FROM CENTRAL EUROPE AND UKRAINE: A NEW METHODOLOGICAL APPROACH. The analysis of the mortality structure was based on the following premises: (1) the mortality structure may be derived from frequency distribution of the categories of the age at death and, (2) the mortality structure may be considered as a complex relational system which ought to be investigated on bothj the elementary and synthetic levels. In the first case, particular trait is analysed in view of the mean age at death. In second case, there are analysed the linear combinations of elementary traits (here, by use of the principal components method).
DIFFERENTIATION OF THE MORTALITY STRUCTURE'IN MESOLITHIC, NEOLITHIC AND EARLY BRONZE AGE POPULATIONS FROM CENTRAL EUROPE AND UKRAINE: A NEW METHODOLOGICAL APPROACH